Revision of Menippus (Coleoptera: Chrysomelidae: Galerucinae) of Taiwan and Menippus dimidiaticornis species group with a new generic synonymy - Lee, Chi-Feng; Bezdĕk, Jan; Suenaga, Haruki (Zootaxa, 2012)
The genus Issikia Chûjô, 1961 has been reduced to a junior synonym of Menippus Clark, 1864. Three Taiwanese species of Menippus are recognized: M. asahinai (Chûjô, 1962), new combination (originally described in Issikia); M. sericea (Weise, 1889), status revived (hitherto misidentified as the Taiwanese population of M. dimidiaticornis); and M. hsuehleeae, new species from north Taiwan. Menippus dimidiaticornis species group is a cluster of six species including M. sericea and four new species namely M. nepalensis, new species from Nepal; M. gressitti, new species from Laos, Vietnam, and China (Hainan); M. beeneni, new species from China (Shaanxi, Shanxi); and M. murzini, new species from Thailand, Laos, and Cambodia.